Cementless 3D Printed Highly Porous Titanium-Coated Baseplate Total Knee Arthroplasty: Survivorship and Outcomes at 2-Year Minimum Follow-Up - Sultan, Assem A.; Mahmood, Bilal; Samuel, Linsen T.; Stearns, Kim L.; Molloy, Robert M.; Moskal, Joseph T.; Krebs, Viktor E.; Harwin, Steven F.; Mont, Michael A. (The Journal of Knee Surgery, 2020)
Newer generation cementless total knee arthroplasty (TKA) implants continue to develop with demonstrated clinical success in multiple recent reports. The purpose of this study was to investigate (1) survivorship, (2) complications, and (3) clinical outcomes of a newer generation cementless and highly porous titanium-coated base plate manufactured using three-dimensional (3D) printing technology. We reviewed a single-surgeon, longitudinally maintained database of patients who underwent primary TKA using cementless, highly porous titanium-coated base plate implants from July 1, 2013 to December 31, 2016. A total of 523 patients were identified. Of this cohort, 496 patients had a minimum of 2-year follow-up and were included in our final analysis. Among these patients, 72 had bilateral TKA yielding a total of 568 TKAs. There were 133 men and 363 women who had a mean body mass index of 33 kg/m2 (range, 20–61 kg/m2). The mean age was 66 years (range, 33–88 years). Average follow-up was 36 months (range, 24–48 months). Indications for TKA included osteoarthritis in 432 patients (87%), rheumatoid arthritis in 40 patients (8%), and knee osteonecrosis in 24 (5%) patients. Implant survivorship was defined as any revision leading to explantation of the base plate for any reason. Kaplan–Meier analysis was performed to determine all-cause implant survivorship at final follow-up for every patient. Complications were assessed using the Knee Society standardized list of TKA complications. Clinical outcomes were determined using the Knee Society pain and function scores. Range-of-motion values were also collected. There were a total of four failures, all were due to aseptic loosening with a survivorship rate of 99% at mean follow-up of 3 years (95% confidence interval = 0.984–0.999). In addition, there were a total of 12 surgical and 10 medical complications. Surgical complications did not affect the base plate or result in any additional implant revisions. A total of nine patients had thromboembolic disease complications; all received medical treatment and recovered adequately. Radiological evaluation did not show any signs of loosening or failures in other patients at final follow-up. Knee Society Scores for pain and function improved from 55 and 56 points preoperatively to 92 and 84 points at 2 years postoperatively. Our results are in concordance with the excellent clinical outcomes and survivorship demonstrated for the newer generation cementless TKA implants. In our experience, 3D printed titanium base plates demonstrated clinical success and excellent survivorship at minimum follow-up of 2 years.
Keywords: total knee arthroplasty; cementless; survivorship; complications